Differential climatic conditions drive growth of Acacia tortilis tree in its range edges in Africa and Asia. Issue 2 (14th February 2023) - Uni, Daphna; Lerner, David; Smit, Izak; Mzimba, Duduzile; Sheffer, Efrat; Winters, Gidon; Klein, Tamir
Abstract: Premise: Tree growth is a fundamental biological process that is essential to ecosystem functioning and water and element cycling. Climate exerts a major impact on tree growth, with tree species often requiring a unique set of conditions to initiate and maintain growth throughout the growing season. Still, little is known about the specific climatic factors that enable tree growth in savannah and desert tree species. Among the global tree species, Acacia tortilis occupies one of the largest distribution ranges (crossing 6500 km and 54 latitudes), spanning large parts of Africa and into the Middle East and Asia. Methods: Here we collected climate data and monitored Acacia tortilis tree growth (continuous measurements of stem circumference) in its southern and northern range edges in South Africa (SA) and Israel (IL), respectively, to elucidate whether the growth–climate interactions were similar in both edges. Results: Growth occurred during the summer (between December and March) in SA and in IL during early summer and autumn (April–June and October–November, respectively). Surprisingly, annual growth was 40% higher in IL than in SA. Within the wide distribution range of Acacia tortilis, our statistical model showed that climatic drivers of tree growth differed between the two sites. Conclusions: High temperatures facilitated growth at the hot and arid IL site, while high humidity permitted growth at the more humid SA site. Our results confer an additional understanding of tree growth adaptation to extreme conditions in Acacia 's world range edges, a major point of interest with ongoing climate change.